2021
DOI: 10.1080/17480272.2021.1958918
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and comparison of two moisture content measurement methods for in situ monitoring of beech laminated veneer lumber

Abstract: A timber bridge constructed in 1815 was renovated in 2018, wherein the load-bearing system was reinforced with beech laminated veneer lumber (LVL) elements. Beech LVL is primarily found in dry and heated structures (Service Class 1). Although the material of this bridge would not be directly exposed to weather, it would be exposed to outdoor relative humidity ranging between 50% in spring and 90% or higher in autumn (Service Class 2). Thus, the moisture content development in the reinforcements was monitored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Therefore, it cannot be suggested with certainty that a different calibration for the two different measurement depths will be necessary for all BB-Q panels in general. However, the three calibrations of "BauBuche" in this study are close to one another in relation to solid beech, and they display a nearly perfect agreement with data from Schiere et al [23] obtained with different types of electrodes and different panels. Due to the assumption on temperature correction, the range of application should be limited to heated indoor conditions where the MC does not vary in an extreme manner.…”
Section: Limitationssupporting
confidence: 89%
See 3 more Smart Citations
“…Therefore, it cannot be suggested with certainty that a different calibration for the two different measurement depths will be necessary for all BB-Q panels in general. However, the three calibrations of "BauBuche" in this study are close to one another in relation to solid beech, and they display a nearly perfect agreement with data from Schiere et al [23] obtained with different types of electrodes and different panels. Due to the assumption on temperature correction, the range of application should be limited to heated indoor conditions where the MC does not vary in an extreme manner.…”
Section: Limitationssupporting
confidence: 89%
“…Therefore, if not for the simplicity of a two-parameter model, the authors recommend using model B for the calibration of R to MC for "BauBuche". The three calibrations of this study appeared to agree very well to a calibration for "BauBuche S" from Schiere et al [23], as shown in Figure 4a, and the beech LVL calibrations indeed differed from a calibration for solid European beech wood [26].…”
Section: Calibration Modelssupporting
confidence: 71%
See 2 more Smart Citations
“…This accumulation of moisture may lead to mould, mildew, health-related problems, and in extreme cases, cause wood components to rot, leading to structural failures. For lumber-based construction, these problems are caused by exposure of wood to high relative humidity levels over extended periods of time [1,2]. Several techniques exist today for measuring MC in wall assemblies, but these methods have high uncertainties when implemented during long-term field testing due to sensor drift and external sources of damage such as dust, rust, corrosion, etc.…”
Section: List Of Figuresmentioning
confidence: 99%